PELUANG DAN TANTANGAN “BIG DATA” DALAM MEMBANGUN “SMART CITY” UNTUK SISTEM TRANSPORTASI - Dian Wahyudin (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2018)
This article aims to provide an overview of the opportunities and challenges of "Big Data" in building "smart city" for transportation systems. The method of research in this paper is descriptive qualitative by using literature review as primary data and synthesis from several journals both international and national. In this digital era, big data can be used by business people in determining business strategy. As for academics can be used as innovation in doing research, although there are still obstacles. For the government can be used as the basis for references to issue policies in building smart city especially transportation system that pay more attention to environmental factors and quality of life of the community so as to support sustainable development program